2021
DOI: 10.1088/1755-1315/939/1/012053
|View full text |Cite
|
Sign up to set email alerts
|

Study on the influence of the cotton storage process on the quality indicators of fiber and yarn

Abstract: This article defines fiber quality indicators that differ in laboratory conditions from the upper, middle and lower layers of Bukhara-6 breeding varieties of cotton, in the modern system HVI 1000 SA. Based on the results of the study, histograms of changes in the quality of cotton fiber in the layers of the harem are presented. As an alternative, the quality indicators of yarn obtained in the laboratory spinning device “Sherli” of small size from fiber were determined. As can be seen from the analysis of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Average daily concentration of nitrogen oxide is 0.164 mg/m 3 , which does not exceed MPC (0.2 mg/m 3 ). Maximum single concentration is 0.128 mg/m 3 , which also does not exceed MPC [9,10].…”
Section: Resultsmentioning
confidence: 82%
“…Average daily concentration of nitrogen oxide is 0.164 mg/m 3 , which does not exceed MPC (0.2 mg/m 3 ). Maximum single concentration is 0.128 mg/m 3 , which also does not exceed MPC [9,10].…”
Section: Resultsmentioning
confidence: 82%
“…If the speed of the air flow is further reduced, then after 18 m/s the particles of fibrous materials fall to the bottom of the pipe and move unevenly, bouncing. The results of monitoring the process of air transportation of fibrous materials showed that the raw materials are unevenly transferred to the pipes of pneumatic transport [5][6][7]. As a result, the cotton moves in separate sections in the pipe, somewhere concentrated, and somewhere in a rarefied state.…”
Section: Introductionmentioning
confidence: 99%
“…The cleaning efficiency, in turn, was 42.9-54.4%, and an increase in the hot air velocity from 2.5 m/s to 7.0 m/s was found to accelerate the evaporation of moisture from the cotton. Studies of several researchers [13][14][15][16] showed that the temperature of cotton fiber in the technological process of cotton ginning was recommended to be 45-50 0 C, in this case, the moisture content of cotton was considered to be optimal for the ginning process. Based on the above analysis, it can be said that in order to achieve high cleaning efficiency of raw cotton, the process of crushing and shaking of raw cotton, which is transferred to ginners, leads to intensive spillage of contaminants in cotton, facilitating further spillage of contaminants.…”
Section: Introductionmentioning
confidence: 99%